Determination of nitrogen and acrylic / styrene components in nitrocellulose systems by UATR and NIRA infrared techniques - Taynara Alves de Carvalho (Elsevier, 2021)
Nitrocellulose (NC) is a polymer of great interest in the aerospace and paint/coating fields. However, there are gaps regarding quantitative analysis. Fast and accurate methodologies for the quality control of raw materials are limited. In this context, the determination of the nitrogen content in NC and the contents of different acrylic/styrene components in formulations with NC were assessed. The applicability of non-conventional Fourier transform infrared spectroscopy (FT-IR) techniques, using the universal attenuated total reflection (UATR) mode, in the medium infrared (MIR) region and of the transflectance in the near infrared region (NIRA) were evaluated. For nitrogen determination, FT-MIR/UATR analysis proved to be the most accurate methodology. For the analysis of acrylic/styrene components in NC, it was possible to determine, with good precision, the contents of most samples by FT-MIR/UATR and FT-NIRA.